2021
DOI: 10.47836/pjst.29.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Built Features and Planting Works during Construction, Maintenance and Renewal Stages at Urban Parks in Petaling Jaya, Selangor

Abstract: Carbon emissions in Malaysia are escalating due to rapid urbanisation wherein their sources are claimed to be generated by the construction industry, including urban park development. Upon completion of the urban park project, the vegetation will supposedly function immediately as a carbon sequester. However, the processes of building, maintaining, and renewing built features and plantings can emit additional carbon dioxide (CO2) than the storage. Rigorous CO2 release across the maintenance and renewal stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…As for Malaysia, a tropical country rich in forest resources, many studies emphasize the preservation of the carbon storage capacity of forests, reduction in carbon-intensive manual maintenance, and expansion of urban forests as critical means to mitigate carbon emissions [92].…”
Section: Research Trend and Agendamentioning
confidence: 99%
“…As for Malaysia, a tropical country rich in forest resources, many studies emphasize the preservation of the carbon storage capacity of forests, reduction in carbon-intensive manual maintenance, and expansion of urban forests as critical means to mitigate carbon emissions [92].…”
Section: Research Trend and Agendamentioning
confidence: 99%
“…For instance, according to Hisham et al, the reason for this is the excessive use and transportation of construction machinery [15]. Jamirsah et al substantiated the above study and concluded that urban parks are carbon sources rather than carbon sink mediums [7]. They analyzed the carbon footprint of urban parks that have been in operation for 18-24 years and reported that about 27.5-40.0% of carbon dioxide was emitted in the construction stage and 10.5-20% in the maintenance stage, whereas only about 29% of carbon dioxide was stored in the urban park.…”
Section: Introductionmentioning
confidence: 99%
“…Parks and green spaces built by the landscape architecture sector use plant materials, so researchers focus on sequestering or storing carbon dioxide that is beneficial to humans rather than carbon dioxide emissions. This leads to the recognition of the provision of urban parks and green spaces as a solution to reduce carbon emissions and air purification [7,8]. In fact, the Korean government is calling for the creation of green areas in living areas, such as urban forests and gardens, as part of the "Korea 2050 Carbon Neutrality Strategy for the Realization of a Sustainable Green Society" [9].…”
Section: Introductionmentioning
confidence: 99%